Tinjauan Holistik Pengajaran Bahasa Indonesia bagi Penutur Asing di UIN Walisongo: Pendekatan Inovatif dengan Model CIPP - Lestari, Citra Rizky; Fahmy , Zulfa; Wati, Maulida Laily Kusuma; Wagiran, Wagiran; Subyantoro, Subyantoro (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study aims to evaluate the effectiveness of the BIPA program and provide recommendations for continuous improvement. The research method used is the CIPP evaluation method which includes context, input, process, and product analysis. Data were collected through interviews and classroom observations. The results showed that in the context aspect, the BIPA program at UIN Walisongo has been adjusted to the needs and cultural background of foreign students. The input aspect shows that the curriculum and teaching materials have been well organized, although they still need some improvements to better suit the latest developments in language teaching. In the process aspect, it was found that interactive teaching methods and the use of information technology have increased students' active participation in learning. However, there are challenges in terms of classroom management and adaptation of teaching methods for different levels of students' language ability. The product aspect showed that the program succeeded in significantly improving foreign students' Indonesian language proficiency, although there is still room for improvement especially in speaking and writing skills. This study concludes that the evaluation approach with the CIPP model can provide a comprehensive view of the BIPA program at UIN Walisongo